2021
DOI: 10.3390/ijms22115432
|View full text |Cite
|
Sign up to set email alerts
|

METTL8 mRNA Methyltransferase Enhances Cancer Cell Migration via Direct Binding to ARID1A

Abstract: The association of RNA modification in cancer has recently been highlighted. Methyltransferase like 8 (METTL8) is an enzyme and its role in mRNA m3C modification has barely been studied. In this study, we found that METTL8 expression was significantly up-regulated in canine mammary tumor and investigated its functional roles in the tumor process, including cancer cell proliferation and migration. METTL8 expression was up-regulated in most human breast cancer cell lines tested and decreased by Yin Yang 1 (YY1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…However, Schöller et al have found that knockout of METTL8 in a pancreatic cancer cell line can reduce cell growth. This finding is consistent with prior studies that have identified frameshift mutations in METTL8 in colorectal cancers and upregulation of METTL8 in breast cancer, an observation further documented by Schöller et al in many types of cancers (Lee et al 2021;Yeon et al 2018). Moreover, Schöller et al have found that METTL8-deficient human cells exhibit reduced respiratory chain activity and respiratory complex assembly.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Schöller et al have found that knockout of METTL8 in a pancreatic cancer cell line can reduce cell growth. This finding is consistent with prior studies that have identified frameshift mutations in METTL8 in colorectal cancers and upregulation of METTL8 in breast cancer, an observation further documented by Schöller et al in many types of cancers (Lee et al 2021;Yeon et al 2018). Moreover, Schöller et al have found that METTL8-deficient human cells exhibit reduced respiratory chain activity and respiratory complex assembly.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with prior studies that have identified frameshift mutations in METTL8 in colorectal cancers and upregulation of METTL8 in breast cancer, an observation further documented by Schöller et al . in many types of cancers ( 55 , 56 ). Moreover, Schöller et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the four m3C associated genes shared the same expression pattern among several cancer types (containing BRCA, LIHC, LUAD, PAAD, and READ), which implied that they all function as oncogenes in these cancers. As described above, METTL8 had been proved to be an oncogene in BRCA with its direct m3C modification on the mRNA of ARID1A [ 17 ], while METTL6 shown a tendency of amplification in malignant breast cancer patients [ 13 ]. Interestingly, compared with METTL8 and METTL6, differential expression of METTL2A in BRCA tumor tissues and adjacent normal tissues was more significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative mRNA splicing research reported that one of the isoforms of METTL8, METLL8-iso1, had been investigated to be transported to mitochondrial with the assistance of its N-terminal mitochondrial targeting sequence [ 11 ]. Aside from the classical m3C32 modification of mitochondrial tRNAs, upregulated of METTL8 by Yin Yang 1 (YY1) transcription factor mediated the m3C modification on the mRNA of AT-rich interactive domain-containing protein 1A and attenuated its translation, which induced the migration of breast cancer cell lines [ 17 ]. In addition, the SUMOylated METTL8 induces the R-loop formation and promotes tumorigenesis in colorectal cancer [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, METTL2A and METTL2B are required for the threonyl and argininyl tRNA methylation, while METTL8 is for mRNA. The expression levels of METTL8 in most breast cancers are upregulated, mediated by the transcription factor Yin Yang 1 (YY1), which in turn modify AT-rich interactive domain-containing protein 1 A (ARID1A) to promote tumor growth and the migration of cancer cells 22 . On the other hand, METTL6 is a tRNA Ser -specific m 3 C methyltransferase, whose knockdown would substantially reduce the susceptibility of lung cancer cells to cisplatin 23 .…”
Section: Introductionmentioning
confidence: 99%